Fuel Price Fluctuation and SME Financial Performance: A Case Study of the Agricultural Sector in Kagadi Town Council. - Bitaka, Raymond (Kabale University, 2024)
This research examines the impact of fuel price fluctuations on the financial performance of small and medium-sized enterprises (SMEs) in the agricultural sector of Kagadi Town Council. The study aimed to evaluate how fuel price volatility affects SMEs, identify the factors influencing fuel prices, and explore the strategies SMEs use to mitigate these effects. A mixed-methods approach, combining quantitative analysis and qualitative interviews, was employed to collect data from SMEs in Kagadi Town Council. The findings indicate a significant negative correlation between fuel price fluctuations and SME financial performance, suggesting that rising fuel prices lead to higher operational costs and reduced profitability for agricultural SMEs. The analysis of fuel price determinants highlights the roles of global oil prices, geopolitical tensions, exchange rates, government policies, and market demand. Additionally, the study identifies several preventative measures adopted by SMEs, such as investing in fuel-efficient technologies, employing hedging strategies, diversifying energy sources, optimizing transportation routes, and renegotiating contracts with suppliers and customers. The research underscores the vulnerability of SMEs to external economic factors like fuel price volatility and emphasizes the need to understand fuel price determinants and implement effective preventative measures. Policy recommendations include stabilizing fuel prices, promoting domestic production and alternative energy sources, and providing support programs and incentives to help SMEs build resilience against fuel price fluctuations. Overall, this research contributes to the existing literature on the relationship between fuel price fluctuations and SME financial performance, offering insights for policymakers, industry stakeholders, and SMEs on managing fuel price volatility and sustaining long-term growth and profitability in the agricultural sector of Kagadi Town Council.